Analysis of investment decisions based on homeowners' stated preferences: Policy measures, smart technologies and financing options - Benedikt Maciosek; Mehdi Farsi; Sylvain Weber; Martin Jakob (University of Neuchâtel, Institute of Economic Research (IRENE), 2022)
Various energy investments are possible in residential buildings. Owners' opportunities are moreover extending with smart technologies and optimisation options, as well as with the rise of collective investment projects. In this context, we investigate owners' investment decisions by conducting a discrete choice experiment that includes all these elements. Our experiment allows evaluating the willingness-to-pay (WTP) for investing in energy efficiency and for purchasing renewable energy. The effect of several energy policies is also investigated using treatment information messages displayed to randomly selected respondents. The results based on our sample of 1,451 Swiss homeowners suggest that WTP for energy investments is positive but marginally decreasing, so that it may be insufficient for very sophisticated and expensive investments. A general paradigm shift is not evident from our results, as the respondents prefer investing alone rather than collectively. Also, load management and storage appear to be valued only in combination but not separately. Amongst all policies, only for a binding CO2 cap per square meter of the accommodation a significant effect can be detected.
Keywords: D12; L94; Q41; 330; Energy efficiency; Renewable energy; Choice experiment; Conditional logit models